216k views
3 votes
Help asap plz? Thank you

Help asap plz? Thank you-example-1
User Kakkalo
by
5.8k points

1 Answer

2 votes

Answer:

y = f(x) = ( x + 4 )( x - 1 )( x - 3 )

Explanation:

Let the equation of the curve drawn on the graph is y = f(x)

We have to find an expression for f(x).

If we take y = 0, then there will be three values of x which are -4, 1 and 3.

Since, there is three solutions of f(x) = 0, hence, f(x) will be a three degree polynomial. and ( x + 4 ), ( x - 1 ) and ( x - 3 ) will be the three factor of the equation.

Therefore, y = f(x) = ( x + 4 )( x - 1 )( x - 3 ) is the required equation of the graph. (Answer)

User Miguel Peniche
by
5.5k points